Sedentary behavior and reduced muscle mass in older adults: a population-based study - Martins Resende, Talita Inácio; Meneguci, Joilson; Eidi Sasaki, Jeffer; da Silva Santos, Álvaro; Damião, Renata (O Mundo da Saúde, 2017)
The loss of muscle mass in older adults is negatively associated with health, which makes it necessary to identify modifiable behavioral habits that may aggravate this condition in this population. In this context, the objectives of the present study were to describe the characteristics of older adults according to reduced muscle mass status and verify its association with sedentary behavior. This was a cross-sectional population-based study, conducted in 24 cities in the Regional Healthcare Administration of Uberaba/Minas Gerais. Older adults (≥ 60 years) from both sexes meeting the inclusion criteria answered a structured questionnaire on sociodemographic, health, and habits information. Participants also underwent measurement of anthropometric variables. Sitting time was measured using the validated questions from the IPAQ. The chi-square statistic was used to examine differences between the prevalence of reduced muscle mass and sociodemographic variables, health and habits. Poisson regression was used to analyze the association between reduced muscle mass and exposure to sedentary behavior. Results: 3.223 older adults with mean age of 70 years (SD = 7.26) took part in the study. Of these total, 20.9% (n = 674) presented reduced muscle mass, being statistically different according to age, schooling, marital status, monthly family income, waist circumference, body mass index, smoking and sedentary behavior. According to the adjusted analysis, older adults who spent ≥ 330 minutes/day sitting demonstrated higher likelihood for reduced muscle mass (PR = 1.18; CI95%: 1.04-1.34). Prolonged sitting time is associated with reduced muscle mass in older adults.